Identifikasi Jumlah Nitrogen(N) dalam Biochar terhadap Hasil Substitusi Amonium Nitrat(NH4NO3) dan Waktu Perendaman dari Limbah Pertanian - Rosiana Bola, Fermina ; Deti Bay, Selfiana (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Biomass waste is a waste that is commonly found in the community that has not been maximally utilized. Biomass waste can be used to make biochar. The raw materials used for making biochar are coconut shells, rice straw, and chicken manure. This raw material is found in many communities. Biochar is a carbon-rich solid material resulting from the conversion of organic waste or agricultural biomass waste through incomplete combustion using a pyrolysis process. The pyrolysis process is a thermochemical decomposition of organic matter through a heating process without or little oxygen. There are 3 types of pyrolysis processes that are often used, but in this study the slow pyrolysis with a temperature of 300-500 ?C and the time used 2-4 hours. At the time of the pyrolysis process there is evaporation so that the nitrogen content of the raw material decreases. Nitrogen is a very important element for repairing damaged soil structures due to excessive use of inorganic fertilizers. The low content of  N elements in the soil can inhibit plant growth and damage the nutrients contained in the soil, so ammonium nitrate is added which aims to enrich nitrogen. Ammonium nitrate concentration used was 5%, 15%, and 25% with 1.2, and 3 weeks soaking time. The difference in concentration and soaking time aims to see or compare the quality of the biochar produced. To determine the nitrogen content in biochar, it was analyzed using the Kjeldahl method.